Whisky eller tonic? Narrativ eksistensteologi - Brorson, Mikael (Dansk Teologisk Tidsskrift, 2021)
At least since Svend Bjerg’s doctoral dissertation, narrative and existentialist theology has, in a Danish context, been considered to be fundamentally opposed to each other. The main goal of the present article is to question this dichotomy. The theoretical foundation for this is an evaluation of the strength of Bjerg’s critique of Rudolf Bultmann and his program of demythologization. This is succeeded by a new interpretation of Johannes Sløk’s authorship focusing on the category of ‘proclamation’, which points to the practical possibility of formulating a narrative existentialist theology, utilizing insights from both theological traditions.